Predictors in ASD: The Importance of Parents' Perception - Mira Coelho, Alda; da Conceição, Virgínia (Frontiers in Psychiatry, 2021)
Several predictors may influence children's developmental trajectories with Autism Spectrum Disorder (ASD), and parents' concerns may play an important role. This study aimed to investigate developmental trajectories of two groups of children with ASD to understand predictive factors, including parental perception. We examined the clinical features of a sample of 55 children with ASD at 3 and 6 years of age in two moments of evaluation to understand this process. We used the Autism Diagnostic Observation Schedule, (ADOS) in both moments. We selected two groups based on ADOS results at moment two: one group with a worse outcome (ADOS results above 8) and one group with a better outcome (ADOS results below 8 in the second moment). We also selected questions from a questionnaire (elaborated by the authors and used in clinical practice) applied to parents to understand if early parents' concerns may help to predict ASD prognosis. We found a significant association between imitation and playability and the child's prognostic. Also, Interactive Gestures, Beginning of Joint Attention, Reciprocity, and Pleasure in Interaction might help identify positive case evolution. Our findings are significant in early intervention program development, not only with direct intervention with the child but also including the parents' involvement in the intervention.